Pembangunan Rumah TOGA dan Kebun TOGA sebagai Kawasan Konservasi TOGA di Desa Rambipuji - Al Yazid, Moch. Khofi; Firdausy, Camelia Puspita; Muhyidin, Ahmad; Putri, Rinad Alamanda; Nabilah, Arfan; Himmah, Anisatul; Esti, Putri Annora; Dewi, Tyas Cahya; Pangaribowo, Dian Agung (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Rambipuji Village is a village in Rambipuji District, Jember Regency, which has the potential for family medicinal plants (TOGA). However, based on the survey conducted, the potential of TOGA in Rambipuji Village has not been optimized, both in terms of cultivation and utilization. To address these problems, the Ormawa BEM Faculty of Pharmacy PPK Team built a TOGA conservation area in the form of a TOGA House and TOGA Garden. The research method used in this community service activity is the Asset Based Community Development (ABCD) approach, which prioritizes the utilization of assets and potential that exist within and are owned by the community in Rambipuji Village. The construction of the TOGA House and TOGA Garden was carried out in July 2024. The result of this program is the establishment of a conservation area in the form of a TOGA House and TOGA Garden in Rambipuji Village. These two conservation areas have become TOGA cultivation centers that can later be managed by the community. It is hoped that, with the existence of this conservation area, the potential of TOGA in Rambipuji can be further optimized.